Inductive Thinking of Junior High School Students in Solving Number Pattern Problems Based on Mathematical Thinking Theory - Ira Kurniawati Ira; Imam Sujadi; Arum Nur Wulandari; Riki Andriatna; Yuli Bangun Nursanti (Universitas Pendidikan Ganesha, 2026)
The development of mathematical thinking is an important goal in mathematics learning because it relates to students’ ability to solve problems through various reasoning processes, including inductive thinking methods. However, students’ application of inductive thinking in solving mathematical problems still requires further exploration. This study aims to explore the application of inductive thinking methods in solving number pattern problems based on the perspective of mathematical thinking. The research employed a qualitative descriptive approach involving three students representing high, medium, and low levels of mathematical ability. Data were collected through a reasoning test and interviews and analyzed through data reduction, data display, and conclusion drawing. The results show that the high ability student was able to identify patterns but still experienced difficulty in formulating accurate generalizations. The medium ability student recognized some patterns but was not able to generalize correctly, while the low-ability student experienced difficulties from understanding the problem to determining general rules. These findings indicate differences in students’ inductive thinking across levels of mathematical ability. The study implies the importance of designing mathematics learning that encourages pattern exploration and generalization processes to support students’ mathematical thinking development.